(1,2)*-Generalized Continuous Map in Fuzzy Bitopological Spaces - P. Saravanaperumal; S. Murugesan (International Journal of Mathematics And its Applications, 2015)
In this paper, we introduce (1,2)*-Fuzzy generalized continuous maps and (1,2)*-Fuzzy$\ddot{{g}}$ continuous maps and study their relations with existing generalized (1,2)*-Fuzzy continuous maps.